2011
DOI: 10.1590/s1516-35982011000100010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização da caatinga e da dieta de novilhos fistulados, na época chuvosa, no semiárido de Pernambuco

Abstract: RESUMO -Um experimento foi conduzido para caracterizar uma caatinga manipulada e estimar a composição botânica e qualidade da dieta de novilhos fistulados. O experimento foi conduzido no período chuvoso, entre março e julho de 2003.A caatinga foi pastejada por 24 novilhas das raças Guzerá e Girolando e dois novilhos esôfago-fistulados. Na caatinga, foram identificados 24 famílias, 38 gêneros e 41 espécies nos dois estratos estudados (dessas, dez espécies foram encontradas na dieta dos animais). As massas de fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
1
7
1
5
Order By: Relevance
“…Average NDIP value was 86.07 for leaves and 575.8 g/kg CP for stems. Results found in this study were higher than those found by Moreira et al (2006) and Ydoyaga Santana et al (2011), evaluating the rainy period, for leaves and similar for stems. AIP averaged 671.7 g/kg CP for leaves and 637.7 g/Kg CP for stems, reflecting Caatinga nutritional reality as a forage source.…”
Section: Resultscontrasting
confidence: 82%
See 3 more Smart Citations
“…Average NDIP value was 86.07 for leaves and 575.8 g/kg CP for stems. Results found in this study were higher than those found by Moreira et al (2006) and Ydoyaga Santana et al (2011), evaluating the rainy period, for leaves and similar for stems. AIP averaged 671.7 g/kg CP for leaves and 637.7 g/Kg CP for stems, reflecting Caatinga nutritional reality as a forage source.…”
Section: Resultscontrasting
confidence: 82%
“…CP amounts during collection months were 169.6 and 89.9 g/kg DM for leaves and stems, respectively. These results were similar for leaves and lower for stems compared to those found by Ydoyaga Santana et al (2011), 164.7 g/kg DM, Evaluating the caatinga's chemical composition in the rainy season. Leaf NDF contents were similar between the first and third month, differing from the second month, with average results of 482.1 and 715.6 g/kg DM for leaves and stems, respectively.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…, Santana et al . ). Conversely, crop stands are expected to remain free of forest invasion due to regular weeding before land abandonment.…”
Section: Discussionmentioning
confidence: 97%